2012
DOI: 10.3109/09273948.2012.670360
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Infliximab in the Treatment of Behçet’s Disease

Abstract: Infliximab therapy is an effective biologic agent for the treatment of ocular inflammation in Behçet's disease unresponsive to the standard immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
1
6
0
3
Order By: Relevance
“…In uveoretinitis, a large number of case reports/ series [Munoz-Fernandez et al 2001;Sfikakis et al 2001;Capella and Foster, 2012;Alokaily et al 2010;Olivieri et al 2008;Takamoto et al 2007;Merino et al 2006;Lindstedt et al 2005;Lanthier et al 2005;Wechsler et al 2004;Sayarlioglu et al 2004a;Rosenbaum, 2004;Giansanti et al 2004;Falappone et al 2004;Morris et al 2003;Gulli et al 2003;Triolo et al 2002;Takayama et al 2013], open-label clinical trials Handa et al 2011;Giardina et al 2011;Tanaka et al 2010;Adan et al 2010;Al-Rayes et al 2008;Tognon et al 2007;Niccoli et al 2007;Accorinti et al 2007;Tugal-Tutkun et al 2005;Benitez-del-Castillo et al 2005;Arayssi et al 2005;Sfikakis et al 2004;Ohno et al 2004;Cantini et al 2012;Keino et al 2011], and nonrandomized comparative studies Yamada et al 2010;Markomichelakis et al 2011] showed that intravenous infliximab, as single therapy, is effective in inducing prompt suppression of ocular inflammation, decreasing the frequency of uveitis attacks and allowing gradual tapering of corticosteroids (CS). As would be expected, vision of eyes with permanent lesions due to irreversible retinal damage does not improve.…”
mentioning
confidence: 99%
“…In uveoretinitis, a large number of case reports/ series [Munoz-Fernandez et al 2001;Sfikakis et al 2001;Capella and Foster, 2012;Alokaily et al 2010;Olivieri et al 2008;Takamoto et al 2007;Merino et al 2006;Lindstedt et al 2005;Lanthier et al 2005;Wechsler et al 2004;Sayarlioglu et al 2004a;Rosenbaum, 2004;Giansanti et al 2004;Falappone et al 2004;Morris et al 2003;Gulli et al 2003;Triolo et al 2002;Takayama et al 2013], open-label clinical trials Handa et al 2011;Giardina et al 2011;Tanaka et al 2010;Adan et al 2010;Al-Rayes et al 2008;Tognon et al 2007;Niccoli et al 2007;Accorinti et al 2007;Tugal-Tutkun et al 2005;Benitez-del-Castillo et al 2005;Arayssi et al 2005;Sfikakis et al 2004;Ohno et al 2004;Cantini et al 2012;Keino et al 2011], and nonrandomized comparative studies Yamada et al 2010;Markomichelakis et al 2011] showed that intravenous infliximab, as single therapy, is effective in inducing prompt suppression of ocular inflammation, decreasing the frequency of uveitis attacks and allowing gradual tapering of corticosteroids (CS). As would be expected, vision of eyes with permanent lesions due to irreversible retinal damage does not improve.…”
mentioning
confidence: 99%
“…20 The use of TNF-alpha inhibitors in treatment of such conditions has been well established, and in recent years there have even been an increasing number of publications attesting to the benefits of TNF-alpha inhibitors for uveitis. [34][35][36][37][38][39] In contrast, there are few studies supporting the use of TNF-alpha inhibitors for the treatment of scleritis. Doctor et al showed that of 10 patients treated with infliximab for refractory scleritis between 2003 and 2007, 9 (90%) showed a decrease in inflammation (after a mean duration of 13.2 weeks) and 6 (60%) were able to cease all other forms of immunosuppression.…”
Section: Discussionmentioning
confidence: 97%
“…Evidencia de aftas orales, acompañadas de por lo menos una de las siguientes lesiones: oculares, genitales y cutáneas (1,3,15,16,17). Asimismo, se debe sospechar con la asociación de otras manifestaciones, como artritis, lesiones gastrointestinales y vasculares, y compromiso del sistema nervioso central (4,18,19,20).…”
Section: Manifestaciones Otorrinolaringológicas De La Enfermedad De Bunclassified
“…El tratamiento depende del grado de compromiso sistémico, e incluye antiinflamatorios esteroideos e inmunomoduladores tópicos y sistémicos, colchicina, dapsona, talidomida, metotrexate, cliclofosfamida, ciclosporina, azatioprina y agentes inhibidores del interferón alfa, como el infliximab (1,3,4,20,24).…”
Section: Manifestaciones Otorrinolaringológicas De La Enfermedad De Bunclassified